2019
DOI: 10.3390/molecules24162907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Abiotic Factors on Triterpenoid Biosynthesis and Saponin Secretion in Marigold (Calendula officinalis L.) in Vitro Hairy Root Cultures

Abstract: The aim of the study was the evaluation of the efficiency of selected abiotic elicitors, i.e., silver and cadmium ions, ultrasound, and UV-C irradiation, in the stimulation of triterpenoid biosynthesis, accumulation, and saponin secretion in Calendula officinalis hairy root cultures. Apart from the possible enhancement of triterpenoid production, the relationship between primary and secondary metabolism (represented respectively by sterols and pentacyclic triterpenes), modifications of the sterol compositional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Elicitation is currently one of the most practically feasible and most effective strategies for enhancing the production of phytochemicals in plant biotechnology [ 8 , 9 , 10 , 11 , 12 ]. In this context, HRCs can serve as a suitable model for the investigation of the influence of different biotic and abiotic elicitors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elicitation is currently one of the most practically feasible and most effective strategies for enhancing the production of phytochemicals in plant biotechnology [ 8 , 9 , 10 , 11 , 12 ]. In this context, HRCs can serve as a suitable model for the investigation of the influence of different biotic and abiotic elicitors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calendula officinalis hairy roots, induced by transformation with the wild-type Rhizobium rhizogenes strain ATCC 15834, produce bioactive triterpenoid saponins, i.e., glycosides of oleanolic acid (OA), and excrete these compounds into the culture medium [ 23 ]. The previous studies revealed that this culture can serve as a suitable research model for investigations on various aspects of productivity improvement, e.g., optimization of culture media [ 24 ] or elicitation with various abiotic and biotic factors [ 13 , 14 , 25 ]. Apart from the main goal of the study, i.e., the assessment of the possible intensification of triterpenoid production, the performed studies involved the determination of steroid content, which allowed the monitoring of the relationship between triterpenoid and steroid pathways, parallel after squalene cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Elicitors are stress inducers that stimulate secondary pathways resulting in the synthesis of bioactive compounds. Abiotic and biotic elicitors were employed in vitro to induce a large quantity of bioactive compounds (alkaloids, alkamides, glucosinolates, terpenes, saponins, flavonoids, steroids, phenolics, and coumarins) within a short period of time [ 6 , 7 , 8 ]. Elicitors of fungal, bacterial, and yeast extract (YE), heavy metals, and hormonal origin were studied for various bioactive compound synthesis [ 6 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the growth-defense trade-off resource hypothesis, one should expect that overlapping metabolic pathways which connect general and specialized metabolism can influence competition and productivity of plant in vitro cultures, including adventitious and hairy roots. Concerning sterols and triterpenoids, the competition mostly appears after squalene cyclization, which has previously been demonstrated in many experiments on wild-type cultures [ 59 , 61 , 62 , 66 ]. This effect was often particularly spectacular after treatment with elicitors such as jasmonic acid (JA) or methyl jasmonate (MeJA) [ 59 , 61 ], indicating a regulatory mechanism in plant defense exists.…”
Section: Discussionmentioning
confidence: 80%
“…It was assumed that some of the functions of these compounds, including regulation of membrane fluidity and permeability or serving as precursors of brassinosteroids, may be involved in plant defense against fungal attack [ 59 ]. Enhancement of sterol and triterpenoid saponin biosynthesis was also observed during elicitation of C. officinalis hairy roots with abiotic factors like cadmium and silver ions, ultrasounds, and UV-C radiation [ 66 ]. The main phenomenon observed as a response to heavy metal treatment was the stimulation (up to 12-fold) of saponin secretion, which was accompanied by significant changes in sterol composition.…”
Section: Sterols and Triterpenoids In Hairy Roots—parallel Enhancementmentioning
confidence: 99%